2021
DOI: 10.1108/inmr-12-2019-0151
|View full text |Cite
|
Sign up to set email alerts
|

Network orchestration: new role of business incubators?

Abstract: Purpose The purpose of this paper is to analyze the performance of incubators in the stages of formation and development of incubated business networks, especially in bottom-up and top-down network models. Design/methodology/approach The research is defined as qualitative and descriptive, with the application of multiple case studies, in which two networks of incubated businesses were investigated, one being top-down and the other bottom-up, which emerged within the incubation process of two business incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Mahmood et al (2015) in their study on business incubators and their impact on economic development in Pakistan found that business incubators played a crucial role in creating, nurturing and sustaining SMEs. In addition, Antunes et al (2021) describe the economic and fiscal impacts of one business incubator to illustrate how an incubator can encourage jobs and income in a local community. According to them Incubators generate jobs and income and create linkages with firms inside and outside the local economy over the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mahmood et al (2015) in their study on business incubators and their impact on economic development in Pakistan found that business incubators played a crucial role in creating, nurturing and sustaining SMEs. In addition, Antunes et al (2021) describe the economic and fiscal impacts of one business incubator to illustrate how an incubator can encourage jobs and income in a local community. According to them Incubators generate jobs and income and create linkages with firms inside and outside the local economy over the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of the entrepreneurial ecosystem, incubators also work with various stakeholders to help entrepreneurs access critical information (Indiran, Khalifah, Ismail 2017) and create business networks (Soetanto, Jack 2013;Antunes, de Castro, da Costa Mineiro 2021). BIs also may act as intermediaries or international intermediaries (Gao et al, 2021) to promote collaborations between entrepreneurs, universities, corporations, and venture markets.…”
mentioning
confidence: 99%